Nature-Based Solutions for Climate Change Adaptation and Sustainable Urban Drainage in Tropical Coastal Cities: a Case for Mombasa City - Velibeyoğlu, Koray; Suleiman Haji, Haji Kidui (01. Izmir Institute of Technology, 2021)
Climate change is a reality, and its impact is being experienced all over the globe. The effects range from heat waves, rising sea levels, coastal erosion, flooding, drought, and reduction of bio-diversity among others. Urban areas are at greater risk since they accommodate the majority of the global human population exceeding 55% and are expected to be 68% by 2050. The most affected urban areas are the tropical coastal cities since most of them fall within low and middle-income countries with low levels of economic development and technological capabilities hence a low capacity to adapt. This study focuses on exploring Nature-Based Solutions (NBS) as an affordable and ecologically sustainable approach to enhance climate change adaptability in tropical coastal cities. A case study of Mombasa is considered, a typical tropical coastal city located in Kenya. Primary data sources including pictures and key informant interviews via snowball sampling were employed to gather ground information. Secondary sources consisted of institutional data review, strategic documents, policies, and scientific journals on NBS and Climate Change adaptation in tropical environments. The study findings depicted the climate change associated challenges in Mombasa include urban flooding, rising sea levels, coastal erosion, increasing temperatures. Rapid urbanization related challenges include inadequate infrastructure and services, poor liquid and solid waste management and inadequate housing. The study proposes NBS measures such as coastal vegetation restoration, implementing green infrastructure in the urban area, and creeks restoration could offer multi-dimensional benefits that can be replicated in other tropical coastal cities to enhance sustainability and climate resilience.

İklim değişikliği bir gerçektir ve etkisi tüm dünyada yaşanmaktadır. Bu etkilerin arasında ısı dalgaları, deniz seviyelerinin yükselmesi, kıyı erozyonu, sel, kuraklık ve diğerleri arasında biyo-çeşitlilik kaybı bulunmaktadır. Güncel durumda kentsel alanlar küresel nüfusun %55'inden fazlasını barındırdığı ve 2050 yılına kadar %68'e kadar artacağı beklendiği için daha büyük risk altındadır. En çok etkilenen kentsel alanlar tropik kıyı şehirleridir, çünkü çoğu düşük ekonomik kalkınma ve teknolojik yeteneklere sahip düşük ve orta gelirli ülkeler kategorisindedir ve bu da onların uyum sağlama kapasitesinin düşük olmasına neden olmaktadır. Bu çalışma, tropikal kıyı kentlerinde iklim değişikliğine uyum sağlamak için uygun fiyatlı ve ekolojik olarak sürdürülebilir bir yaklaşım olarak doğaya dayalı çözümleri (NBS) keşfetmeye odaklanmaktadır. Kenya'da bulunan tipik bir tropikal kıyı kenti olan Mombasa vaka çalışması olarak ele alınmıştır. Zemin bilgilerini toplamak için kartopu örneklemesi yoluyla resimler ve önemli muhbir görüşmeleri de dahil olmak üzere birincil veri kaynakları kullanılmıştır. İkincil kaynaklar, kurumsal verilerin gözden geçirilmesi, stratejik belgeler, politikalar ve NBS ve tropikal ortamlarda iklim değişikliğine uyum ile ilgili bilimsel dergilerden oluşuyordu. Çalışma bulguları, Mombasa'daki iklim değişikliği ile ilgili zorlukların kentsel sel, yükselen deniz seviyeleri, kıyı erozyonu, artan sıcaklıklar olduğunu göstermiştir. Hızlı kentleşme ile ilgili zorluklar arasında yetersiz altyapı ve hizmetler, zayıf sıvı ve katı atık yönetimi ve yetersiz konut bulunmaktadır. Çalışma, kıyı bitki örtüsünün restorasyonu, kentsel alanda yeşil altyapının uygulanması ve derelerin restorasyonu gibi NBS önlemlerinin sürdürülebilirliği ve iklim direncini arttırmak için diğer tropikal kıyı şehirlerinde çoğaltılabilecek çok boyutlu faydalar sunabileceğini önermektedir.
Tropikal Kıyı Kentlerinde İklim Değişikliğine Uyum ve Sürdürülebilir Kentsel Drenaj için Doğaya Dayalı Çözümler: Mombasa Şehri Örneği
Thesis (Master)--Izmir Institute of Technology, City and Regional Planning, Izmir, 2021
Includes bibliographical references (leaves. 125-138)
Text in English; Abstract: Turkish and English
Keywords: Mombasa City; Nature-based solutions; Tropical coastal cities; Climate change; Ecosystem-based approaches